Dynamical Analysis on Traveling Wave of a Reaction-Advection-Diffusion Equation with Double Free Boundaries (Journal of Partial Differential Equations, 2021)
This paper investigates a reaction-advection-diffusion equation with double free boundaries. The stationary solution of the system is studied by phase planeanalysis. Then, the scale logarithm change sequence method is introduced to show theexact heteroclinic of the system with corresponding parameters. Moreover, a completedescription of the types of traveling wave solutions is given with different advectionterm coefficients.